Efeito imunomodulador de Saccharomyces boulardii em camundongos experimentalmente infectados por Toxocara canis - Avila, Luciana Farias da Costa de (2013)
Human toxocariasis is a zoonotic disease with high prevalence in developing countries and it has been considered one of the most prevalent helminthiasis in Latin America. Probiotics modulate the immune response, which open up a new perspective of their use for prevention and treatment of parasitic diseases. To study the possible mechanisms of action mediated by the probiotic Saccharomyces boulardii, the aim of this study was to evaluate its immunomodulatory effect in Toxocara canis experimentally infected mice. Initially an in vitro test was performed to assess the existence of harmful effect of probiotic on T. canis. Next, was evaluated the modulation of the immune response of Swiss mice supplemented with S. boulardii and experimentally infected by T. canis. To this end the expressions of IL- 12, IL-17, IL-10, IL-4 and IFNγ cytokines in spleen cells from mice at 24 and 48h post- infection were studied by quantitative polymerase chain reaction (qPCR). The results indicate that the probiotic has no direct effect on parasites larvae, suggesting that is necessary the contact of S. boulardii with the intestinal mucosa of the host to the development of its protective effect. Furthermore S. boulardii promoted reduction of approximately 40% of the number of T. canis larvae recovered. Supplementation with S. boulardii modulated by increasing the expression of IL-12 (7 times), IL-17 (42 times) after 24h of infection and IFNγ (43 times), in uninfected mice. Splenic expression modulation of IL-10 was reduced by half in 48h of infection supplemented mice, and the IL-4 expression showed no difference between groups under the studied conditions. Modulation of innate immunity observed in S. boulardii supplemented mice suggests the elevation of IL-12 and IL-17 as one of the mechanisms involved in the resistance by this probiotic to T. canis infection.